塞荷的教育知識論探究 - 許宏儒; Hung-Ju Hsu (教育研究與評鑑中心, 2014)
本文旨在探討法蘭西學術院院士Michel Serres（米歇爾‧ 塞荷）的教育知識論。當前全球高等教育機構正積極推展通識教育，重新省思以往以學科作為知識分界的教學方式。但若要真正的將知識連「通」起來，成為通識教育，就必須從知識論典範上的根本分析與反思，並從基本知識的細微分子上，重新解構，再加以融合。塞荷認為知識不應該分為自然科學與人文科學。他希冀的是交融自然科學與人文科學的混合的知識形式，一種知識火焰的模式。而這種交融是一種尋「西北航道」之旅的教育知識論。塞荷並針對這種知識論的形式，初步規劃出大學一年級的共同課程。而事實上，通識教育的「通」應由形容詞轉換為「動詞」，其核心在於培養學生自發與自動地跨越分化的知識領域，自我建構具有組織性、聯結性的意義世界。塞荷的教育知識論，即旨在教育出能不斷跨越疆界，通向異質之處的「博學的第三者／知識的吟遊者」。這也是未來「明日之人」（l’homme de demain）的可能圖像。 This article investigates French Academician––Michel Serres’ educational epistemology. Nowadays, individual discipline as the only means of teaching knowledge has been in question in higher education in the world. Thus, liberal education is taken into consideration as one of the most important reform of curriculum. However, concerning about the liberal education, we cannot but analyze and interrogate the fundamental epistemology of disciplines, deconstruct their elements and reintegrate them. From Serres’ point of view, he argues that we can not divide the knowledge into the natural science and the human science. His educational epistemology is a flame-knowledge where the natural science and the human science mix into. He also designs common programs for the first years of College. In fact, the main idea of liberal education is to form students as a self-organization man who is capable of constructing a meaningful, organized and connected world by himself; and to form students as a human who like to spontaneously transgress the boundary of discipline and knowledge. Therefore, his educational epistemology seeks the “North West Passage” between all knowledge and hopes to come into being a “troubadour of knowledge” who will never stop transgressing, mixing all knowledge, learning, and being toward others. The “troubadour of knowledge” represents the future picture of “a man of tomorrow.”